Theological foundations of the political power ontology - Schelkunov, Mikhail Dmitrievich; Volchkova, Olga Olegovna; Krasnov, Anton Sergeevich (Linguistics and Culture Review, 2021)
The article is devoted to the study of the normative and theological foundations of political power origin and belongs to the field of political theology research. Despite the narrow field of research, the work is devoted to the study of a separate aspect of social life as a whole. The study of the theological foundations of political power was carried out within the framework of the neoinstitutional methodological paradigm, taking into account the data of hermeneutic analysis, which is an applied aspect of the work. Political power is considered by the authors in the framework of a broader aspect - the ontology of the social, as part of the fundamental layer of being. The authors, within the framework of the theological paradigm, considered the main ontological concepts of the political, analyzed the correlation of key political concepts - "power", "authority", and "sovereign". Various positions on understanding the essence of political power, as well as on the origin of this phenomenon in the historical and theological key are considered, the points of view of both domestic and foreign experts are studied.